Corrosion chimique comparée du grès Calcaire Sinémurien et du Calcaire Bajocien de Lorraine Belge - Souchez, R. (ERDKUNDE, 1963)
This publication compares chemical weathering of two limestones under the same climate: the Sinemurien Limestone and the Bajocien Limestone of southern Belgium. The worked out spring waters do not contain Mg++ , Na++ , K+ (98% Ca++) by a good approximation. From then on, the content in Ca(HCO3)2 is the smallest of the following two: a proportion of Ca++ and a proportion of HCO3-. The waters of the Sinemurien limestone have 20° TAC (French degrees of hardness) and those of the Bajocien limestone only 15.8°. But the Sinemurian limestone contains 65% CO3Ca and the Bajocian limestone 90%. The explanation is not found in wide-open fractures, but in porosity: from 14% to 17% for the Sinemurian sand-limestone and from 4% to 8% for the Bajocien limestone. So, in order to understand limestone morphology, we need to consider the physical properties of the limestones.